Arthroscopic study of the elbow joint in dog cadavers - Tatarunas,Angelica Cecilia (2006)
PURPOSE: To study the arthroscopic technique of the elbow joint in dog cadavers. The possibility to see the intra articular structures, technical difficulties and complications which occurred during the procedure were analyzed. METHODS: ten dog's cadavers (twenty elbow joints) were examined. Both, arthroscopic and instrumental portals were performed on the medial site of joint at caudal and cranial positions, respectively. RESULTS: We could see the totality of the proposed structures. The main complications were cartilage iatrogenic lesion and periarticular infiltration. CONCLUSION: The elbow arthroscopy in dogs permits detailed intra-articular visualization. The arthroscopic and instrumental portals were simple to be done.